The medieval constitution of liberty : political foundations of liberalism in the West - Salter, Alexander William; Young, Andrew T. (University of Michigan Press, 2023)
Salter and Young point to the constitutional order that characterized the High Middle Ages. They provide a historical account of how this constitutional order evolved following the fall of the Western Roman Empire. This account runs from the settlements of militarized Germanic elites within the imperial frontiers, to the host of successor kingdoms in the sixth and seventh centuries, and through the short lived Carolingian empire of the late eighth and ninth centuries and the so called feudal anarchy that followed its demise.